153k views
5 votes
Given f(x) = x - 7 and g(x) = x2.
Find g(f(4)).
g(f(4)) =

User Insaner
by
5.4k points

2 Answers

5 votes

Answer:

9

Explanation:

edg 2020

User OXXO
by
5.0k points
6 votes

Answer:

Explanation:

If we are looking to find the composition of g(f(4)), we start at the innermost part of the problem which is to evaluate f(4).

If f(x) = x - 7, then f(4) = 4 - 7. f(4) = -3.

Now take that -3 and evaluate the g(-3).

If g(x) = x^2, then g(-3) = (-3)^2 which is 9.

Therefore, f(g(4)) = 9

User Myrtle
by
5.8k points